Toxicity risk from glucocorticoids in sarcoidosis patients. (November 2017) - Khan, Nauman A.; Donatelli, Christopher V.; Tonelli, Adriano R.; Wiesen, Jonathan; Ribeiro Neto, Manuel L.; Sahoo, Debasis; Culver, Daniel A.
Abstract: Background: Glucocorticoids (GC) are considered first-line therapy for treating sarcoidosis, but there are few data about the adverse consequences of GC. Although there are several steroid-sparing medications available for treatment, a large proportion of patients are treated with prolonged courses of GC. The toxicities of GC in sarcoidosis populations have not been carefully evaluated. Methods: We performed a retrospective cohort study of all newly diagnosed sarcoidosis patients who had the entirety of their medical care in a single health system. We analyzed the time to development of a composite toxicity end-point, including diabetes, hypertension, weight gain, hyperlipidemia, low bone density and ocular complications of GC using Cox proportional hazards analysis. Results: One hundred and five patients were ever treated with GC, whereas 49 were not treated during a median follow-up of 101 months. GC-treated patients developed 1.3 ± 1.1 toxicities during therapy, versus 0.6 ± 1.0 in the non-treated group. After adjustment for age, gender, race and preexisting conditions, the hazard ratio for ever-treated patients was 2.37 (1.34–4.17) for the composite end-point. Age and the presence of preexisting conditions also were associated with reaching the end-point. Similar effects were seen when analyzed for cumulative GC dose and for duration of GC use. For individual end-points, weight gain (HR 2.04) and new hypertension (HR 3.36) were associated with any use of GC. Conclusions: Our data suggest that GC are associated with clinically important toxicities in sarcoidosis patients, associated with both the cumulative dose and duration of treatment. Highlights: Standard therapy of sarcoidosis includes steroids, often in prolonged courses. Long-term steroids for sarcoidosis are associated with significant comorbidity. Steroid therapy in sarcoidosis needs to be re-evaluated and minimized when possible.